Rupture Uterus in a Tertiary Care Centre: A Descriptive Cross-sectional Study - Deepa Chudal; Sebak Shrestha; Ruby Shrestha; Vikash Paudel (Journal of Nepal Medical Association, 2021)
Introduction: Rupture uterus is an obstetric catastrophe with poor maternal and fetal outcome. The objective of the study is to determine the prevalence of rupture uterus in pregnancy.